Pengaruh Pengalaman Auditor Terhadap Kualitas Audit Di KAP - Arnita, Vina; Diana, Yana; Andini Puspita Sari (ARBITRASE: Journal of Economics and Accounting, 2023)
Companies have several important considerations when determining which public accounting firm (KAP) will audit their financial statements. The company definitely wants to ensure that the KAP chosen has a good reputation and is credible, thus providing confidence that the audit will be carried out with professionalism and integrity. With the experience and expertise of the KAP, it is expected that the KAP will have an in-depth understanding of industry conditions and applicable accounting requirements, and can provide added value in auditing financial statements. This study aims to determine the factors that influence the company in the selection of KAP Big Four and Non Big Four. The population used in this research is all companies going public on the IDX in 2020-2022. The sample selection was carried out using purposive sampling, and 2,040 data were collected. By using multiple logistic regression, the results show that total assets turnover, company complexity, and the diversity of audit committee members affect the likelihood of a company choosing the Big Four KAP. On the other hand, the company's growth has no effect on the possibility that the company will choose the Big Four KAP.